Figure 2 in Selective predation on common voles by Tawny Owls and Long-eared Owls in winter and spring ... - Balčiauskas, Linas; Received, Laima Balčiauskienė; Online, Published (Zenodo, 2014)
Figure 2. Distribution of the body mass of Microtus arvalis individuals, preyed upon by Strix aluco and Asio otus in winter and spring 2004–2005, as estimated from mandibles: A) in the winter-spring diet of Asio otus; B) in the winter diet of Strix aluco; C) in the spring diet of Strix aluco. ... : Published as part of Balčiauskas, Linas, Received, Laima Balčiauskienė & Online, Published, 2014, Selective predation on common voles by Tawny Owls and Long-eared Owls in winter and spring, pp. 242-249 in Turkish Journal of Zoology 38 (1) on page 246, DOI: 10.3906/zoo-1303-20, http://zenodo.org/record/13192107 ...